Manual of structural kinesiology - Floyd R T (New York: Mc Graw Hill Education, 2013)
"Explaining the process of human movement, Manual of Structural Kinesiology gives a straightforward view of human anatomy and its relation to movement. The manual clearly identifies specific muscles and muscle groups and describes exercises for strengthening and developing those muscles. Manual of Structural Kinesiology provides important information in an accessible format through a combination of logical presentation, illustrations, and concise writing style"--
"In this revision, I have attempted to fi ne tune the chapters for increased consistency and clarity while maintaining the successful presentation approach the late Dr. Clem Thompson established from 1961 through 1989. I fi rst used this book as an undergraduate and later in my teachings over the years. Having developed great respect for this text and Dr. Thompson's style, it is my intention to continue to preserve the effectiveness of this time-honored text, while adding material pertinent to the professions working with today's ever-growing physically active population. Hopefully, I have maintained a clear, concise, and simple presentation method supplemented with applicable information gained through my research and career experiences"--
Keywords: Kinesiology; Human Locomotion; Muscles; Sports Medicine; Sports; Physical Education; Arts